Anteseden dan Konsekuen Realisasi Belanja Modal Pada Provinsi di Indonesia - Arifahtun Zohrah; Suyanto Suyanto (Jurnal Riset Akuntansi & Perpajakan (JRAP), 2017)
ABSTRACT The purpose of this research is to examine the antecendent of Government Expenditure Realization, whether there is influence of Original Local Income (PAD) and Balance Fund against Government Expenditure Realization, and to examine the consequence of Government Expenditure Realization, whether there is influence of Government Expenditure Realization against Economic Growth. The population of this research is 33 Provinces of Indonesia, and used secondary data of Government Budgets-realization of Indonesia Provinces from 2009 until 2013. This research used multiple regression in antecendent of Government Expenditure Realization testing and simple regression in consequence of Government Expenditure Realization testing. The hypothesis testing consist of coefficient of determination test, F test, and t test. The research revealed that in antecendent of Government Expenditure Realizationtesting, partially Original Local Income (PAD) variable and Balance Fund variable influence Government Expenditure Realization, and in Consecuent Government Expenditure Realization testing, partially Government Expenditure Realization influence Economic Growth. ABSTRAK Tujuan dari penelitian ini adalah untuk menguji Anteseden Realisasi Belanja Modal yaitu pengaruh Pendapatan Asli Daerah dan Dana Perimbangan terhadap Realisasi Belanja Modal, serta untuk menguji Konsekuen Realisasi Belanja Modal yaitu pengaruh Realisasi Belanja Modal terhadap Pertumbuhan Ekonomi. Populasi dalam penelitian ini adalah Provinsi di Indonesia, dan menggunakan data sekunder yang berupa Laporan Realisasi Anggaran (LRA) tahun 2009 sampai dengan tahun 2013. Penelitian ini menggunakan regresi berganda dalam pengujian Anteseden Realisai Belanja Modal dan regresi sederhana untuk pengujian Konsekuen Realisasi Belanja Modal. Uji hipotesis terdiri dari uji koefisien determinasi, uji F, dan uji t. Hasil penelitian menunjukkan bahwa dalam pengujian Anteseden Realisasi Belanja Modal, secara parsial Pendapatan Asli Daerah dan Dana Perimbangan berpengaruh terhadap Realisasi Belanja Modal, dan dalam Pengujian kosekuen, Realisasi Belanja Modal secara parsial berpengaruh terhadap Pertumbuhan Ekonomi. JEL Classification: M40